Concordance between Different Criteria for Metabolic Syndrome in Peruvian Adults Undergoing Bariatric Surgery - Echevarria-Castro, Nataly (2022)
Background: Metabolic Syndrome (MetS) is a clinical entity that has been linked to several non-communicable diseases. There are various consensuses to determine its presence, such as the IDF, ALAD, Harmonized, AHA/NHLBI, NCEP-ATP III or AACE criteria. However, there is currently no standardization to properly identify it. Objective: To assess the diagnostic concordance between different criteria for MetS in Peruvian adults undergoing bariatric surgery. Methods: We conducted a secondary analysis of the institutional database of a bariatric clinic located in Lima, Peru. We obtained data from adults between 18–59 years who underwent bariatric surgery (Roux-en-Y Gastric Bypass or Sleeve Gastrectomy). According to the Kappa coefficient, a heatplot was designed to analyze the concordance of the criteria. Results: An almost perfect concordance was found between all criteria except AACE. The highest kappa coefficient (κ = 0.980) was recorded between the IDF and ALAD criteria using all the sample. Similar results were obtained when we stratified by sex. Conclusions: This study shows that, excluding the AACE, different criteria for metabolic syndrome could be used in Latino adults undergoing bariatric surgery with similar results. Given the postoperative implications, we believe that IDF and ALAD would be the best options in our population.